Rivaroxaban-Associated Hepatotoxicity: a Clinical Case and Literature Review - B. A. Tatarsky; N. V. Kazennova; D. A. Napalkov (Рациональная фармакотерапия в кардиологии)
Direct oral anticoagulants (not vitamin K antagonists), unlike standard oral anticoagulants (e.g. warfarin), have a predictable manifestation of the anticoagulant effect and the possibility of using a fixed dose without the need for constant monitoring of the anticoagulant effect. The rapid onset and cessation of the effect of direct oral anticoagulants, the relatively low likelihood of interaction with food and other drugs compared to warfarin, have expanded the possibilities of anticoagulant therapy.Direct oral anticoagulants, particularly rivaroxaban, are widely used for deep vein thrombosis/pulmonary embolism prevention and treatment, and for stroke prevention in patients with atrial fibrillation. Awareness of side effects is mostly associated with bleeding risks while other problems with the use of this medication attract less physicians’ attention. These side effects mainly include liver damage and some other rare side effects. This article describes a clinical case of rivaroxaban-associated drug-induced liver injury in patient with first diagnosed atrial fibrillation and normal baseline liver enzymes. A literature review focused on this problem is also presented.